Control of seed borne fungi on tomato seeds and their management by botanical extracts - Mehedi, Imam; Sultana, Afia; Raju, Md Amanut Ullah (Research in Agriculture Livestock and Fisheries, 2016)
Seed health test was done in laboratory to determine the status of seed borne fungi on seeds of five tomato (Lycopersicon esculentum) varieties viz. Manik, Ratan, Roma VF, Kopotakkho and Monirumpuri and their possible control by using plant extracts. A total of 4 genera of 3 species of fungi were recorded where Fusarium oxysporum was the most prevalent and predominant seed borne fungus (25.60%). Other three fungal species are Aspergillus sp. of Aspergillus flavus (21.70%) and Aspergillus niger (11.11%) and Cladosporium sp. (13.49%). Tomato seeds were treated with different plant leaf extracts namely Mahogany, Mehendi and Allamanda with different doses viz. 1:1, 1:2 and 1:3 to control the seed borne fungi. In treated seeds, germination was ranged from 72-82% which was 68% in controlled condition. Among the doses of three botanicals, Mahogany, Mehendi and Allamonda extract @ (1:1 w/v) showed significant performance in controlling seed borne fungi and germination of tomato seeds. Among the three botanicals, Mahogany @ (1:1 w/v) was found the best treatment regarding percent reduction of seed borne infection. Res. Agric., Livest. Fish.3(3): 403-410, December 2016